PERFORMANCE OF EAST JAVA OMBUDSMAN IN HANDLING COMMUNITY COMPLAINTS - Hilmi Izaz Robbani; Ananta Prathama (DIA: Jurnal Administrasi Publik, 2022)
The purpose of this research is to determine the performance of the Ombudsman Representative for East Java in handling public complaints, where East Java Province has the most cities and regencies in Indonesia. The method used in this research is descriptive qualitative and has a research focus in assessing the performance of the Ombudsman using Simanjuntak's theory which consists of organizational support, management ability and effectiveness, and the performance of everyone in the organization. The results of this study are that in terms of organizational support, it is quite supportive, in terms of the ability and effectiveness of the Ombudsman management to work well, and from the performance of everyone in the Ombudsman organization looks very good and has competence. the conclusion is that from the overall assessment it is quite good, it's just that there are problems in human resources and office printers.